Prediction of the Stamped Part Thinning Depending on Its Geometry and Blank Material - Rihacek, Jan; Podany, Kamil; Faltynek, Frantisek (Manufacturing Technology Journal, 2019)
The paper deals with a design of new dimple geometry with a view to minimizing its thinning. In this case, three types of blank materials were analyzed, i.e. ferritic steel X2CrCuTi18, austenitic steel X5CrNi18-10 and austenitic steel X5CrNi18-10 with additional heat treatment. Thinning analysis for different dimple geometry and blank material is performed with a numerical simulation using finite element method in ANSYS software. To verify the accuracy of the numerical simulation, a practical stamping of the part with initial design and comparison between resulting thinning values, which is determined by ANSYS software and experimental microscopic measurement, is also performed.
Keywords: Numerical Simulation; Forming; Dimple; ANSYS; Finite Element Method